Proceedings of the Paris Open Science European Conference OSEC 2022 (Laboratoire d'idées, 2022)
For more than twenty years, the international research community has affirmed its support for open and collaborative practices that improve the quality, transparency, reproducibility and inclusiveness of science. In France, this orientation has been reflected in the adoption of two National Plans for Open Science, in 2018 and 2021. In this context and on the occasion of the French Presidency of the Council of the European Union, France organised the Open Science European Conference (OSEC) on 4 and 5 February 2022. This conference on the transformation of the research and innovation ecosystem in Europe was an opportunity to address in particular transparency in health research, the future of scientific publishing and the opening of codes and software produced in a scientific context, but also the necessary transformations of research assessment, summarised in the Paris Call presented during the event and calling for the creation of a coalition of actors committed to reforming the current system. This international event was organised was organised by the French Académie des sciences, the Ministry of Higher Education and Research, the French National Center for Scientific Research (CNRS), the National Institute of Health and Medical Research (Inserm), the High Council for Evaluation of Research and Higher Education (Hcéres), the National Research Agency (ANR), the University of Lorraine and the University of Nantes.